2018
DOI: 10.1002/ijc.31364
|View full text |Cite
|
Sign up to set email alerts
|

Breast cancer risk in relation to history of preeclampsia and hyperemesis gravidarum: Prospective analysis in the Generations Study

Abstract: Preeclampsia and hyperemesis gravidarum are pregnancy complications associated with altered sex hormone levels. Previous studies suggest preeclampsia may be associated with a decreased risk of subsequent breast cancer and hyperemesis with an increased risk, but the evidence remains unclear. We used data from the Generations Study, a large prospective study of women in the United Kingdom, to estimate relative risks of breast cancer in relation to a history of preeclampsia and hyperemesis using Cox regression ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 52 publications
1
18
2
Order By: Relevance
“…Some studies, including the aforementioned Norwegian study found no association between hyperemesis and risk of breast cancer (80,81). Other studies report an increased risk of breast cancer subsequent to hyperemesis (82,83).…”
Section: Autoimmune Diseasementioning
confidence: 97%
“…Some studies, including the aforementioned Norwegian study found no association between hyperemesis and risk of breast cancer (80,81). Other studies report an increased risk of breast cancer subsequent to hyperemesis (82,83).…”
Section: Autoimmune Diseasementioning
confidence: 97%
“…In the Generations Study, the association between preeclampsia and breast cancer risk did not vary among women with and without in utero exposure to preeclampsia. 29 Study strengths include the large sample size and prospective design, which is expected to limit differential recall of gestational hypertensive disorders by breast cancer status. The size and diversity of our cohort enabled us to stratify by demographic, lifestyle, pregnancy, and breast cancer characteristics, although we acknowledge reduced precision in some strata.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, a decrease in the insulin-like growth factor in this complication may also play a role in this hypothesis. A number of studies have confirmed the link between breast cancer and preeclampsia (65)(66)(67).…”
Section: Preeclampsiamentioning
confidence: 97%